1998
DOI: 10.1038/sj.onc.1202052
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by Smad3 and down-regulation of Smad3 expression in response to TGF-β in human normal lung epithelial cells

Abstract: Smad family members are essential intracellular signaling components of the transforming growth factor-beta (TGF-b) superfamily involved in a range of biological activities. Two highly homologous molecules, Smad2 and Smad3, have so far been identi®ed as receptor-activated Smads for TGF-b signaling and have become the focus of intensive studies. However, no de®nite di erences in regulation or function have been established between these TGF-b signaling molecules. In the present study, we show that the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 18 publications
7
106
0
Order By: Relevance
“…Repression of SMAD3 mRNA levels in response to TGF␤ has been noted in epithelial and mesangial cells as well as in lung fibroblasts (45)(46)(47). In light of the dependence of TGF␤ signaling intensity on the steadystate levels of its intracellular second messengers, inhibition of SMAD3 expression may thus be a negative feedback mechanism with autoregulatory function to prevent continuous SMAD signaling in response to TGF␤ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Repression of SMAD3 mRNA levels in response to TGF␤ has been noted in epithelial and mesangial cells as well as in lung fibroblasts (45)(46)(47). In light of the dependence of TGF␤ signaling intensity on the steadystate levels of its intracellular second messengers, inhibition of SMAD3 expression may thus be a negative feedback mechanism with autoregulatory function to prevent continuous SMAD signaling in response to TGF␤ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of DPC4/Smad4 in MDCK cells is sufficient to induce the activation of gene transcription, cell cycle arrest, and apoptosis [35]. It has also been shown that constitutive expression of Smad3 did not induce apoptosis, but made human normal epithelial cells more sensitive to TGF-β-induced apoptosis [36].…”
Section: Disscussionmentioning
confidence: 99%
“…JNK and p38 MAPK have been shown to mediate apoptosis induced by many stimuli [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Though it has been shown that TGF-β activates JNK and p38 signaling molecules [21][22][23], their implication in TGF-β-induced apoptosis is not clear.…”
Section: Disscussionmentioning
confidence: 99%
“…It has also been suggested that TGF-␤1 can induce apoptosis in human primary B lymphocytes (19 -21) and BL cell lines (20,(22)(23)(24)(25)(26). The induction of apoptosis by TGF-␤1 has also been observed in myeloid leukemia cells (27), gastric carcinoma cells (28), primary endometrial cells (29), primary hepatocytes and hepatoma cells (30), human cervical carcinoma cell lines (31), and human lung epithelial cell lines (32).…”
mentioning
confidence: 91%